Impact of Cardiovascular Risk Factors on Graft Outcome Disparities in Black Kidney Transplant Recipients. Issue 3 (September 2016) - Taber, David J.; Hunt, Kelly J.; Fominaya, Cory E.; Payne, Elizabeth H.; Gebregziabher, Mulugeta; Srinivas, Titte R.; Baliga, Prabhakar K.; Egede, Leonard E.
Abstract : Although outcome inequalities for non-Hispanic black (NHB) kidney transplant recipients are well documented, there is paucity in data assessing the impact of cardiovascular disease (CVD) risk factors on this disparity in kidney transplantation. This was a longitudinal study of a national cohort of veteran kidney recipients transplanted between January 2001 and December 2007. Data included baseline characteristics acquired through the United States Renal Data System linked to detailed clinical follow-up information acquired through the Veterans Affairs electronic health records. Analyses were conducted using sequential multivariable modeling (Cox regression), incorporating blocks of variables into iterative nested models; 3139 patients were included (2095 non-Hispanic whites [66.7%] and 1044 NHBs [33.3%]). NHBs had a higher prevalence of hypertension (100% versus 99%; P <0.01) and post-transplant diabetes mellitus (59% versus 53%; P <0.01) with reduced control of hypertension (blood pressure <140/90 60% versus 69%; P <0.01), diabetes mellitus (A1c <7%, 35% versus 47%; P <0.01), and low-density lipoprotein (<100 mg/dL, 55% versus 61%; P <0.01). Adherence to medications used to manage CVD risk was significantly lower in NHBs. In the fully adjusted models, the independent risk of graft loss in NHBs was substantially reduced (unadjusted hazard ratio, 2.00 versus adjusted hazard ratio, 1.49). CVD risk factors and control reduced the influence of NHB race by 9% to 18%. Similar trends were noted for mortality, and estimates were robust across in sensitivity analyses. These results demonstrate that NHB kidney transplant recipients have significantly higher rates of CVD risk factors and reduced CVD risk control. These issues are likely partly related to medication nonadherence and meaningfully contribute to racial disparities for graft outcomes. Abstract : Supplemental Digital Content is available in the text.